2019
DOI: 10.1039/c9ra08007d
|View full text |Cite
|
Sign up to set email alerts
|

Comparative investigation of interactions of hydrogen, halogen and tetrel bond donors with electron-rich and electron-deficient π-systems

Abstract: Recently, noncovalent interactions in complexes and crystals have attracted considerable interest. The current study was thus designed to gain a better understanding of three seminal types of noncovalent interactions, namely: hydrogen, halogen and tetrel interactions with p-systems. This study was performed on three models of Lewis acids: X 3 -C-H, F 3 -C-X and F-T-F 3 (where X ¼ F, Cl, Br and I; andT ¼ C, Si, Ge and Sn) and three p-systems as Lewis bases: benzene (BZN), 1,3,5-trifluorobenzene (TFB) and hexafl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
23
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 52 publications
(31 reference statements)
3
23
1
Order By: Relevance
“…For example, the most favorable interaction energies were observed for complexes included BI 3 , where the interaction energies of BI 3 ⋅⋅⋅F 3 N, ⋅⋅⋅Cl 3 N, ⋅⋅⋅Br 3 N, and ⋅⋅⋅I 3 N complexes were observed with values of −1.45, −3.81, −4.46, and −5.18 kcal/mol, respectively. Accordingly, it might be concluded that the + π‐hole interactions of BX 3 with lp‐hole‐containing molecules are exclusive not only to the repulsive/attractive electrostatic interactions but also to the van der Waals interactions with X 3 atoms in X 3 N. These findings match those previously observed, demonstrating the crucial role of X 3 atoms in the interactions of lp‐hole‐containing molecules [21] …”
Section: Resultssupporting
confidence: 87%
See 2 more Smart Citations
“…For example, the most favorable interaction energies were observed for complexes included BI 3 , where the interaction energies of BI 3 ⋅⋅⋅F 3 N, ⋅⋅⋅Cl 3 N, ⋅⋅⋅Br 3 N, and ⋅⋅⋅I 3 N complexes were observed with values of −1.45, −3.81, −4.46, and −5.18 kcal/mol, respectively. Accordingly, it might be concluded that the + π‐hole interactions of BX 3 with lp‐hole‐containing molecules are exclusive not only to the repulsive/attractive electrostatic interactions but also to the van der Waals interactions with X 3 atoms in X 3 N. These findings match those previously observed, demonstrating the crucial role of X 3 atoms in the interactions of lp‐hole‐containing molecules [21] …”
Section: Resultssupporting
confidence: 87%
“…Accordingly, it might be concluded that the + π-hole interactions of BX 3 with lp-hole-containing molecules are exclusive not only to the repulsive/attractive electrostatic interactions but also to the van der Waals interactions with X 3 atoms in X 3 N. These findings match those previously observed, demonstrating the crucial role of X 3 atoms in the interactions of lp-hole-containing molecules. [21] Compared to the previously reported tetrel + σ-hole analogs, the triel + π-hole interactions showed low negative interaction energies. [17] These results outlined the favorable contribution of the three coplanar X 3 atoms of tetrahedral structure in the strength of tetrel interactions than their candidates of the trigonal planar structure of the boron trihalide.…”
Section: Interaction Energymentioning
confidence: 64%
See 1 more Smart Citation
“…The value of the employed PoC to investigate the Chal···PoC distance effect was made equal to the one used in optimization. The strength of the σ-hole and lp hole interactions was estimated in terms of the molecular stabilization energy ( E stablization ) according to the following equation: 12 , 13 , 18 , 34 , 35 …”
Section: Methodsmentioning
confidence: 99%
“…The σ-hole and lp hole interactions will first be investigated from the electrostatic perspective via the point-of-charge (PoC) approach. 12 , 13 , 18 , 34 , 35 In addition, the PoC approach will be utilized to precisely define lp, lp hole, and σ-hole locations. Moreover, the Lewis basicity effect on the strength of the σ-hole and lp hole interactions will be also examined.…”
Section: Introductionmentioning
confidence: 99%